Makna Ᾱṡar Al-Sujud dalam Q.S. Al-Fatḥ [48]: 29 Pendekatan Ma’na-Cum-Maghzā - Syaekhudin (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2024)
This article aims to find the contemporary meaning of the word aṡar al-sujūd found in QS. al-Fatḥ verse 29 with a hermeneutic view of ma'na-cum-maghza. The study was conducted using qualitative methods. The application of this approach to the interpretation of QS. al-Fath verse 29 with attention to aspects of textual-literal analysis combined with contextual analysis. So that based on these two reviews will find the meaning of historical and dynamic phenomenal significance to the interpretation of QS. al-Fath verse 29. The findings show that aṡar al-sujūd in QS. Al-Fath verse 29 describes the radiance, majesty, serenity that appears on the face which is reflected in the obedience, solemnity and humility of the companions.